Physiological responses to ergometer and on-water incremental rowing tests - Vogler, A. J.; Rice, A. J.; Gore, C. J. (International Journal of Sports Physiology and Performance, 2010)
Purpose: This study evaluated the validity of ergometer tests against the criterion of on-water rowing and determined the reliability of field measurements by comparing results between ergometer (ERG) and on-water (OW) tests. Methods: Seven male rowers completed incremental tests on a Concept2 rowing ergometer and in a single scull. Average power output, oxygen consumption (VO2), heart rate (HR), blood lactate concentration (BLa) and distance completed were measured during each ERG and OW workload. Data Treatment: Linear regression between power output and HR, BLa, VO2 and distance allowed submaximal results to be compared between ERG and OW tests at equivalent intensities based on five standard power outputs. Submaximal results were analyzed using repeated measure factorial ANOVAs and maximal data used dependent t tests (P < .05), the magnitude of differences were also classified using effect size analyses. The reliability of repeated measurements was established using Typical Error. Results: Differences between ERG and OW submaximal results were not statistically significant for power output, HR, BLa, and VO2, but distance completed (P < .001) was higher during the ERG test. However, the magnitude of physiological response differences between the ERG and OW tests varied between individuals. Mean HR at anaerobic threshold showed good agreement between both tests (r = .81), but the standard error of the estimate was 9 beats per minute. Conclusions: Individual variation in physiological response differences between ERG and OW tests meant that training intensity recommendations from the ERG test were not applicable to on-water training for some rowers, but provided appropriate prescriptions for most athletes.